Leaf Flavonoid Aglycone Patterns, Ethnobotany and Conservation of Schima wallichii - Joshi, Kunjani (Ecoprint: An International Journal of Ecology, 2009)
Schima wallichii (DC.) Korth (Chilaune) is widely distributed in the various habitats of Himalaya. Information regarding chemical constituents of this species is very limited. During the chemotaxonomic study of some angiosperms, falconoid aglycone : flavonal quercetin was isolated from the leaves of Schima Wallichii using standard procedures after seperation and purification by paper chromatography and TLC (thin layer chromatography) plates in several solvent system, but other falconoid were not detected. The ethno botanical study of Schima Wallichii was also carried out. Various parts and the products of this species are locally used for medicine, fuel and other domestic purposes. This indigenous knowledge can be integrated in the local plan that can help to the poverty alleviation and economic development of the villages. But at present, this plant is under serious threat due to habitat destruction and over-exploitation. A holistic approach is, therefore, essential for the sustainable conversation of this species. In this paper , strategies for conservation of the plant, its resources and habitatshave also been proposed. Key words: Flavonoids; quercetin; ethnobotany; consersation; holistic approach doi: 10.3126/eco.v13i0.1622 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 Page 9-13